2007
DOI: 10.1103/physrevlett.99.216103
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of Work Function Difference in High Order Gundlach Oscillation

Abstract: Gundlach oscillation (or the standing-wave state) is a general phenomenon manifesting in the tunneling spectrum acquired from a metal surface using scanning tunneling spectroscopy. Previous studies relate the energy shift between peaks of the lowest-order Gundlach oscillation observed on the thin film and the metal substrate to the difference in their work functions. By observing Gundlach oscillations on Ag/Au(111), Ag/Cu(111), and Co/Cu(111) systems, we demonstrate that the work function difference is not the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 23 publications
(25 reference statements)
2
60
0
Order By: Relevance
“…The subpeaks are most clearly resolved in the second FER of the h-BN. In fact, it has been shown that the energetic position of the second FER is a good measure to determine relative shifts of the surface potential on the local scale, as it is less influenced by the image potential at the sample surface [65]. Inspecting the internal structure of the second FER for the different parts of the h-BN moiré, we find the three peaks being located at ∼6.0, 6.3, and 6.6 V. The subpeak of lowest energy has its maximum intensity at the pore, while the peak of highest energy shows maximum intensity on the wire region, indicating a reduction of the work function when going from the wire to the pore.…”
Section: Resultsmentioning
confidence: 99%
“…The subpeaks are most clearly resolved in the second FER of the h-BN. In fact, it has been shown that the energetic position of the second FER is a good measure to determine relative shifts of the surface potential on the local scale, as it is less influenced by the image potential at the sample surface [65]. Inspecting the internal structure of the second FER for the different parts of the h-BN moiré, we find the three peaks being located at ∼6.0, 6.3, and 6.6 V. The subpeak of lowest energy has its maximum intensity at the pore, while the peak of highest energy shows maximum intensity on the wire region, indicating a reduction of the work function when going from the wire to the pore.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, their relative changes in energy and line width are much less affected than absolute values. In particular, relative changes within the 2nd Stark-shifted state are the least affected by the field [10].…”
mentioning
confidence: 97%
“…Surface averaged values of energy, dispersion (and lifetime) of image potential states were extensively probed, first by inverse photoemission (IPES) [7] and later by two-photon photoemission spectroscopy (2PPE) [8]. High spatial resolution of an image potential state was achieved by scanning tunneling spectroscopy (STS) [9,10] . The shifts are consistent with a lateral confinement of the electrons as described by textbook (two-dimensional) particle-in-a-box models [14].…”
mentioning
confidence: 99%
See 2 more Smart Citations